A physical and versatile aging compact model for hot carrier degradation in SiGe HBTs under dynamic operating conditions. (January 2020) - Mukherjee, C.; Marc, F.; Couret, M.; Fischer, G.G.; Jaoul, M.; Céli, D.; Aufinger, K.; Zimmer, T.; Maneux, C.
Highlights: A new physical and accurate aging compact model for HCI in modern SiGe HBTs. Developed based on Reaction Diffusion theory and Fick's law of diffusion. The model ensures time invariance in simulation of the degradation characteristics Model validation performed on three advanced technologies and diverse stress conditions. The proposed model is compatible with existing circuit design framework. Efficient model implementation for predicting reliability-aware circuit architectures. Abstract: This paper presents a new physics-based compact model implementation for interface state creation due to hot-carrier degradation in advanced SiGe HBTs. This model accounts for dynamic stress bias conditions through a combination of the solution of reaction-diffusion theory and Fick's law of diffusion. The model reflects transistor degradation in terms of base recombination current parameters of HiCuM compact model and its accuracy has been validated against results from long-term DC and dynamic aging tests performed close to the safe-operating-areas of various HBT technologies.